What Patient Characteristics Influence Nurses' Assessment of Health Literacy?. (1st August 2016) - Goggins, Kathryn; Wallston, Kenneth A.; Mion, Lorraine; Cawthon, Courtney; Kripalani, Sunil
Abstract : Overestimation of patients' health literacy skills is common among nurses and physicians. At Vanderbilt University Hospital, nurses routinely ask patients the 3 Brief Health Literacy Screen (BHLS) questions. Data from 2 studies that recruited patients at Vanderbilt University Hospital—the Health Literacy Screening (HEALS) study and the Vanderbilt Inpatient Cohort Study (VICS)—were analyzed to compare the BHLS score recorded by nurses during clinical care with the score recorded by trained research assistants during the same hospitalization. Logistic regression models determined which patient characteristics were associated with nurses documenting higher health literacy scores than research assistants. Overall, the majority (60%) of health literacy scores were accurate, though nurses recorded meaningfully higher health literacy scores in 28.4% of HEALS patients and 35.6% of VICS patients. In the HEALS cohort, patients who were male and had less education were more likely to have higher health literacy scores recorded by nurses (odds ratio [OR] = 1.93, 95% confidence interval [CI] [1.24, 3.00]; and OR = 0.80, 95% CI [0.74, 0.88], respectively). In the VICS cohort, patients who were older, were male, and had less education were more likely to have higher health literacy scores recorded by nurses (OR = 1.01, 95% CI [1.003, 1.02]; OR = 1.49, 95% CI [1.20, 1.84]; and OR = 0.87, 95% CI [0.83, 0.90], respectively). These findings suggest that health literacy scores recorded by nurses for male patients and patients with less education could be overestimated. Thus, health care professionals should be aware of this tendency and should verify the results of routine health literacy screening tests, especially in certain patient groups.